Una Historia con Aguijón: Mis Aventuras con los Abejorros - Russy Velandia, Lizeth (Góndola, enseñanza y aprendizaje de las ciencias, 2023)
In this review, the book unfolds across 17 chapters documenting the passion and work of conservationist Dave Goulson throughout his life. From childhood, he developed a profound interest in nature and insects, and his interaction with wildlife in his place of residence honed his observational skills, a key characteristic for any researcher. He took his first steps in wildlife conservation by creating gardens to attract bees and other species. Among other activities, he expressed an interest in breeding animals and collecting insect specimens for study. Implicit in his narratives is the changing rural landscape in England, with emphasis on the increase in intensive agricultural practices and the loss of natural habitats that negatively impacted local fauna and flora.